Comparison of National and Local Approaches to Detecting Suicides in Healthcare Settings. Issue 9 (16th March 2019) - Riblet, Natalie B; Shiner, Brian; Watts, Bradley V; Britton, Peter
Abstract: Introduction: In order to address the problem of suicide, healthcare providers and researchers must be able to accurately identify suicide deaths. Common approaches to detecting suicide in the healthcare setting include the National Death Index (NDI) and Root-Cause Analysis (RCA) methodology. No study has directly compared these two methods. Materials and Methods: Suicide reporting was evaluated within the Veterans Affairs (VA) healthcare system. All suicides were included that occurred within 7 days of discharge from an inpatient mental health unit and were reported to the VA through the NDI record linkage and/or RCA database between 2002 and 2014. The proportion of suicide deaths that were identified by NDI and found in the RCA database were calculated. Potential misclassification by the NDI was evaluated, whereby the RCA database identified a suicide case, but the NDI classified the death as a non-suicide. Results: In the study period, the NDI identified 222 patients who died by suicide within 7 days of discharge, while the RCA database only detected 95 reports of suicide. A comparison of cases across the two methods indicated that the RCA database identified only 35% ( N = 78) of NDI detected suicides ( N = 222). Conversely, the RCA database detected 13 suicide cases that the NDI had coded as deaths due to accidental poisoning or other causes. Importantly, RCA accounted for 13% ( N = 7) of overdose suicides identified in all databases ( N = 52). Conclusions: Combining national and local approaches to detect suicide may help to improve the classification of suicide deaths in the healthcare setting.